1997
DOI: 10.1021/bi9712697
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Cavity of Herpesvirus Proteases Revealed by the Crystal Structure of Herpes Simplex Virus Protease/Inhibitor Complex

Abstract: Human herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) are responsible for herpes labialis (cold sores) and genital herpes, respectively. They encode a serine protease that is required for viral replication, and represent a viable target for therapeutic intervention. Here, we report the crystal structures of HSV-1 and HSV-2 proteases, the latter in the presence and absence of the covalently bound transition state analog inhibitor diisopropyl phosphate (DIP). The HSV-1 and HSV-2 protease structures show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 26 publications
4
62
0
1
Order By: Relevance
“…Diagrams of the procapsid and mature head (capsid plus internally coiled DNA) are shown at center (from Figure 1). Ribbon diagrams are shown for the φ29 scaffold (PDB code 1N04, [13 •• ]) and portal/connector (PDB code 1IJG, [9]), the HSV2 protease (PDB code IAT3, [61]), the λ accessory protein (PDB code 1TCZ, [26]) and the HK97 MCP (PDB code 1OHG, [19]). It remains to be seen whether system-to-system variation is accomplished by embellishment of the same basic fold (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Diagrams of the procapsid and mature head (capsid plus internally coiled DNA) are shown at center (from Figure 1). Ribbon diagrams are shown for the φ29 scaffold (PDB code 1N04, [13 •• ]) and portal/connector (PDB code 1IJG, [9]), the HSV2 protease (PDB code IAT3, [61]), the λ accessory protein (PDB code 1TCZ, [26]) and the HK97 MCP (PDB code 1OHG, [19]). It remains to be seen whether system-to-system variation is accomplished by embellishment of the same basic fold (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…2, the 38-kDa sequence fractions matched a portion of the LETV genome containing the overlapping open reading frames corresponding to HSV-1 genes UL26 (minor capsid protein or protease) and UL26.5 (assembly or scaffolding protein). In other herpesviruses, UL26 encodes a polyprotein that is autoproteolytically cleaved to yield protease and another scaffolding protein that is distinct from the assembly or scaffolding protein encoded by UL26.5 (10,18,20). The UL26 LETV homolog is diagrammed with these putative cleavage sites ( Fig.…”
mentioning
confidence: 99%
“…3a, lane 1). On the basis of homologs of UL26 in other herpesviruses, this gene encodes a polyprotein that is autoproteolytically cleaved during expression and yields the assembly protein and protease (10,18,20). The two expressed LETV proteins likely correspond to these protein products.…”
mentioning
confidence: 99%
“…They exist in a monomer-dimer equilibrium in vitro where only the dimer is active [5][6][7]. Xray crystallographic studies on the protease from CMV, HSV1, HSV2, VZV, KSHV and EBV have shown the presence of a conserved dimer structure [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%